Schizophrenia with and without obsessive-compulsive symptoms: a comparative analysis of performance on trail making test and disability on WHODAS. Issue 6 (29th October 2020) - Singh, Apala; Beniwal, Ram Pratap; Bhatia, Triptish; Deshpande, Smita Neelkanth
Abstract : Background: Presence of obsessive-compulsive symptoms (OCS) affects performance on tests of some cognitive functions, such as the trail making test (TMT), and may affect the level of disability in schizophrenia (SZ). Aims: The aim of the present study was to compare performance on TMT and disability on WHO Disability Assessment Schedule (WHODAS) in persons with SZ with and without OCS in a cross-sectional study. Methods: Persons with SZ (n=200) fulfilling DSM-V (Diagnostic and Statistical Manual) diagnostic criteria were assessed on Yale Brown Obsessive Compulsive Scale (YBOCS) and divided into two groups based on presence or absence of OCS. TMT and WHODAS V.2.0 were applied. The two groups as a whole, as well as a subsample matched on age, gender and age of onset were compared. Results: Out of 200 persons with SZ, 37 (18.5%) reported OCS. The OCS group took a significantly longer mean time to complete TMT-A (Z=−3.02, p=0.003) as well as TMT-B (Z=-3.551, p<0.001). Significant correlations were found between TMT-A and total YBOCS Scores (r=0.351, p=0.033), as well as TMT-A and YBOCS compulsion scores (r=0.404, p=0.013) but not with TMT-B Scores. The OCS group reported greater disability in all domains separately as well as on average WHODAS Scores (Z=−5.969, p<0.001). Significant correlations were found between YBOCS obsession scores and YBOCS total scores with average WHODAS Scores (r=0.614, p<0.001 and r=0.406, p=0.013, respectively). We obtained essentially similar results with the matched subsample as well as with the entire group. Conclusion: Persons with SZ and comorbid OCS had significantly poorer performance on TMTs and greater disability in comparison to persons with SZ alone. Magnitude of disability correlated with severity of OCS.